2021
DOI: 10.1172/jci.insight.143643
|View full text |Cite
|
Sign up to set email alerts
|

CMTM6 drives cisplatin resistance by regulating Wnt signaling through ENO-1/AKT/GSK3β axis

Abstract: Rewiring tumor cells to undergo drug-induced apoptosis is a promising way to overcome chemoresistance, therefore identifying causative factors for chemoresistance is of high importance. Unbiased global proteome-profiling of sensitive, early and late cisplatin resistant OSCC lines identified CMTM6 as top ranked up-regulated protein. Analyses of OSCC patient tumor samples demonstrated significantly higher CMTM6 expression in chemotherapy-nonresponders as compared to chemotherapy-responders. In addition, a signif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…In addition, several studies have demonstrated the involvement of this pathway in mediating resistance to chemotherapy and radiation in different types of cancer, including breast (30,34,(62)(63)(64). Wnt signaling is also known to specifically mediate platinum resistance in endometrial cancer (65), ovarian (66), and oral squamous cell carcinoma (67). However, little is known regarding the role of Wnt signaling in mediating resistance to platinum in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have demonstrated the involvement of this pathway in mediating resistance to chemotherapy and radiation in different types of cancer, including breast (30,34,(62)(63)(64). Wnt signaling is also known to specifically mediate platinum resistance in endometrial cancer (65), ovarian (66), and oral squamous cell carcinoma (67). However, little is known regarding the role of Wnt signaling in mediating resistance to platinum in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…We deemed this observation significant since Wnt signaling is intrinsically associated with tumorigenesis, and several studies have demonstrated the involvement of this pathway in mediating resistance to chemotherapy and radiation in different types of cancer, including breast (30,34,(58)(59)(60). Wnt signaling is also known to specifically mediate platinum resistance in endometrial cancer (61), ovarian (62), and oral squamous cell carcinoma (63). Nonetheless, little is known regarding the role of Wnt signaling in mediating resistance to platinum in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of PI3K/Akt signaling prevails in human cancer and Akt often interacts with other signaling pathways involved in EMT/CSC to confer drug resistance. For instance, hypoxia synergistically enhanced gemcitabine-induced interaction between Akt and notch1, which in turn promoted cell stemness and chemoresistance [148] . Akt/glycogen synthase kinase 3-β activated Wnt signaling and promoted stemness and cisplatin resistance [149] .…”
Section: Aktmentioning
confidence: 99%
“…For instance, hypoxia synergistically enhanced gemcitabine-induced interaction between Akt and notch1, which in turn promoted cell stemness and chemoresistance [ 148 ] . Akt/glycogen synthase kinase 3-β activated Wnt signaling and promoted stemness and cisplatin resistance [ 149 ] . Akt cross talks with MAPK and NF-κB inducing overexpression of P-gp and MDR in cancer cells with EMT/CSC phenotypes [ 128 , 150 ] , as well as activating programmed death-ligand 1 expression which leads to immunosuppression [ 147 ] .…”
Section: Pathways Connnecting Emt and Csc And The Implication In Drug Resistancementioning
confidence: 99%